2003
DOI: 10.1002/jcu.10172
|View full text |Cite
|
Sign up to set email alerts
|

Value of contrast‐enhanced power Doppler sonography using a microbubble echo‐enhancing agent in evaluation of small breast lesions

Abstract: Compared with PDUS without contrast enhancement, contrast-enhanced PDUS provides better visualization of the morphology of vascular Doppler signals that is characteristic of malignancy and therefore has a higher sensitivity and diagnostic accuracy, albeit a lower specificity. In differentiating between benign and malignant small breast lesions, contrast-enhanced PDUS can be helpful when used with gray-scale sonography and PDUS without contrast enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
(30 reference statements)
1
19
0
4
Order By: Relevance
“…Despite the care taken in setting the sonographic parameters and reducing movement artefacts, Power Doppler US proved to be unreliable in identifying neoplastic lesions with slow flow and abundant fibrotic component (four malignant lesions were found to be avascular). In addition, two hypervascular lesions interpreted as malignant even after quantitative assessment [radiation intensity (RI) greater than 0.7] turned out to be benign at histology; this finding was in agreement with previous reports [9][10][11], which consider flow velocity and resistive index to be less reliable parameters than the morphological assessment of vessels. Use of the contrast material drastically reduced the number of lesions identified as avascular or hypovascular and correctly defined all neoplastic lesions as malignant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite the care taken in setting the sonographic parameters and reducing movement artefacts, Power Doppler US proved to be unreliable in identifying neoplastic lesions with slow flow and abundant fibrotic component (four malignant lesions were found to be avascular). In addition, two hypervascular lesions interpreted as malignant even after quantitative assessment [radiation intensity (RI) greater than 0.7] turned out to be benign at histology; this finding was in agreement with previous reports [9][10][11], which consider flow velocity and resistive index to be less reliable parameters than the morphological assessment of vessels. Use of the contrast material drastically reduced the number of lesions identified as avascular or hypovascular and correctly defined all neoplastic lesions as malignant.…”
Section: Discussionsupporting
confidence: 91%
“…Acquisitions were limited to the suspicious lesion and part (10 mm) of the surrounding tissue. Lesion vascularity was evaluated on the basis of the number of vessels identified according to the criteria reported in the literature [9] -avascular (no vascular poles), hypovascular (presence of one or two vascular poles), hypervascular (presence of three or more poles) -and enhancement patterns. Spectral analysis with pulsed Doppler was performed to obtain information on flow velocity and resistances.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the sensitivity of CE-US, the peak and flow thresholds could be further lowered, considering also that in our study we did not take into account the obviously benign lesions of the baseline ultrasound examination and that therefore the threshold values used are probably higher than those that could be used by studying a sample including a lesion range from BI-RADS category 2-5. Not all studies reported in the literature allow the definition of thresholds for distinguishing benign lesions from malignancies [20,30,33,34]. Although in our study it was possible to identify threshold values for certain parameters, it should be remembered that the study population was chosen on the basis of a suspect or typically malignant morphological appearance on the baseline ultrasound examination.…”
Section: Discussionmentioning
confidence: 93%
“…The injection of microbubbles may act to enhance the US contrast for the identification and characterization of peritumoral neovasculature. 33 Additionally, the optical perturbation induced by ICG-encapsulated microbubbles may help to identify the contribution of peritumoral neovasculature for enhanced reconstruction accuracy in diffuse optical tomography, with the hypothesis that the spatial extent of the optical contrast is greater than that of the US contrast. 13 For simplicity's sake, the suspicious tissue is divided into three compartments: tumor ͑T͒, peritumoral neovasculature ͑P͒, and background ͑B͒, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%